Surgical outcomes of liver resection for hepatoblastoma in infants versus older children: a bi-centric, propensity-score-matched, comparative study - Fuchs, Juri; Hery, Geraldine; Ruping, Fabian; Fouquet, Virginie; Guerin, Florent; Michalski, Christoph; Günther, Patrick; Branchereau, Sophie (Journal of pediatric surgery, 2026)
Background and aim - Hepatoblastoma (HB) is the most common pediatric liver malignancy, with most patients undergoing surgical resection after neoadjuvant chemotherapy at an age older than one year. Infants (≤12 months) undergoing liver resection represent a distinct and less studied subgroup, considered more vulnerable and at increased surgical risk by some clinicians. This study aimed to compare perioperative outcomes between infants and older children undergoing hepatectomy for HB to determine whether surgery in infancy is associated with increased risks. - Methods - This bi-centric study included all consecutive children who underwent hepatectomy for HB between 2013 and 2023 at two tertiary centers. Patients were divided into two groups: infants (≤12 months) and older children (>12 months). Propensity score matching (PSM) was applied to adjust for confounders, including tumor stage, type of hepatectomy, and vascular involvement. Perioperative outcomes, including blood transfusions, complications, and length of hospital stay, were compared between groups. - Results - Among 109 HB patients undergoing liver resection, 27 (25 %) were infants. After PSM, 25 infants were matched with 25 older children. No significant differences were observed in intraoperative blood transfusion rates, postoperative complications, or hospital length of stay. Major complications (≥Clavien-Madadi grade III) occurred in 7.4 % of infants and 6.1 % of older children. There was no 90-day mortality in either age group. - Conclusion - Liver resection for HB in infants does not appear to carry higher surgical risks compared to older children. These findings support an aggressive surgical approach when indicated, emphasizing the importance of specialized multidisciplinary care. Further prospective studies are needed to refine surgical strategies in this unique patient population.